An update on sterilization and disinfection of endodontic instruments - Vaishnavi Satish Borse; Varsha Sanjay Pandit; Ashwini A Gaikwad; Aishwarya N Handa; Abhijit B Jadhav; Ruchira K Bhamare (Wolters Kluwer Medknow Publications, 2022)
Infection control is a term used to describe the precautions, policies, and procedures undertaken in a healthcare setting in order to minimize the risk of spreading an infection. It helps prevent the transmission of disease-producing agents such as bacteria, viruses, and fungi from one patient to another, from the dental practitioner and dental staff to patients, and from patients to dental practitioner or other dental staff. Among the many aspects of infection control, sterilization and disinfection of instruments and associated appliances play a crucial role for any infection control regimen to be successful in a health-care setting. Sterilization and disinfection of instruments can be described in general as decontamination procedures for treating instruments, enabling their safe usage. Failure to adhere to recommended sterilization guidelines and protocols can lead to serious cross-infection causing a disease which could be far more incapacitating than what the patient was originally suffering from. It also increases the chances of persistence of the infection. In either case, treatment outcomes are drastically reduced, rendering the entire treatment unfruitful. Sterilization and disinfection of instruments are of particular significance in the field of endodontics due to the intrinsic nature of the various procedures involved as part of the field and the type of instruments that are used. Routine decontamination procedures are usually not effective due to the complex, intricate, and minute design of various endodontic instruments. In addition, it is very important to take into account the effect of various sterilization protocols on the material of the instrument. This review article aims to describe the various sterilization and disinfection procedures for endodontic instruments in a concise manner, taking into consideration the potential effects that the sterilization/disinfection procedure might have on the instrument to be sterilized. Hopefully, it will make it easier for clinicians to choose the most suited/appropriate sterilization and disinfection procedure for any given endodontic instrument.